Inverse Scattering for the Problem with Impedance-type Boundary (Journal of Partial Differential Equations, 2000)
This paper deals with the inverse scattering problems for the Helmholtz equation with impedance boundary condition. It aims at reconstructing the unknown impedance coefficient from the knowledge of scattered wave fields. We generalize the concept of classic solution (CS) to optimal solution (OS) by a nonlinear optimization problem. Then, based on potential theory, we establish an inversion procedure to get the approximation of OS which is defined as the regularized solution (RS) in this paper. The convergence result for RS is proven from which one can get OS and CS stably and efficiently.
Keywords: Inverse problem; optimal solution; convergence